2017
DOI: 10.22210/govor.2016.33.03
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of vowels’ F1 and F2 values in frequent English loanwords in Polish and Russian languages

Abstract: SummaryThe paper presents results of an investigation of F1 and F2 formants values in English loanwords uttered by Polish and Russian native speakers during spontaneous speech. Ten participants with an equal level of English language proficiency took part in the experiment. Their stimulated conversation was recorded and English loanwords were extracted from the recordings to investigate the vowels' formants, by means of the Praat software. The F1 and F2 analysis points out that a relationship between the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The set of stimuli was created according to the following rules: (1) all logatomes were in line with the open-syllable principle, the common law in Slavic before the vocalizations of the semivowels; (2) the items consisted of stops /k/, /ɡ/, /p/, /b/, /t/, /d/ and a combination of five common vowels /a/, /ɛ/, /i/, /ɔ/, /u/ which was justified by the degree of interference of plosives with the adjacent vocalic segment (Ladefoged & Maddieson, 1996; Stevens & House, 1963), as well as by the results from previous studies using logatomes in perceptual discrimination, which showed that the diphones “pa,” “si,” and “ki” are among the most discriminable elements (Pascal et al, 1989); (3) to control for a fixed stress position and length of the pseudowords, both bisyllabic CVCV and trisyllabic CVCVCV sequences were used in the test; (4) no zero-onset was present in the tokens, even though this structure is possible in all investigated languages; (5) primarily non-palatalized segments were used due to the unequal distribution and frequency of palatalized CV sequences in the investigated languages; (6) to avoid a priming effect, only non-nasalized units were taken into consideration due to frequent synchronous and asynchronous nasals in Polish (Kudera, 2018) as opposed to other Slavic languages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of stimuli was created according to the following rules: (1) all logatomes were in line with the open-syllable principle, the common law in Slavic before the vocalizations of the semivowels; (2) the items consisted of stops /k/, /ɡ/, /p/, /b/, /t/, /d/ and a combination of five common vowels /a/, /ɛ/, /i/, /ɔ/, /u/ which was justified by the degree of interference of plosives with the adjacent vocalic segment (Ladefoged & Maddieson, 1996; Stevens & House, 1963), as well as by the results from previous studies using logatomes in perceptual discrimination, which showed that the diphones “pa,” “si,” and “ki” are among the most discriminable elements (Pascal et al, 1989); (3) to control for a fixed stress position and length of the pseudowords, both bisyllabic CVCV and trisyllabic CVCVCV sequences were used in the test; (4) no zero-onset was present in the tokens, even though this structure is possible in all investigated languages; (5) primarily non-palatalized segments were used due to the unequal distribution and frequency of palatalized CV sequences in the investigated languages; (6) to avoid a priming effect, only non-nasalized units were taken into consideration due to frequent synchronous and asynchronous nasals in Polish (Kudera, 2018) as opposed to other Slavic languages.…”
Section: Methodsmentioning
confidence: 99%
“…(3) to control for a fixed stress position and length of the pseudowords, both bisyllabic CVCV and trisyllabic CVCVCV sequences were used in the test; (4) no zero-onset was present in the tokens, even though this structure is possible in all investigated languages; (5) primarily non-palatalized segments were used due to the unequal distribution and frequency of palatalized CV sequences in the investigated languages; (6) to avoid a priming effect, only non-nasalized units were taken into consideration due to frequent synchronous and asynchronous nasals in Polish (Kudera, 2018) as opposed to other Slavic languages.…”
Section: Design Of Materialsmentioning
confidence: 99%